Application of analytical hierarchy process in strategy of human resource capacity building at the karya lestari farmers group, Sibaganding Village, Simalungun Regency - Simanjuntak, Friska Irene; Siti Latifah, .; Rahmawaty, .; Ismail, Mohd Hasmadi; Gandaseca, Seca; Karuniasa, Mahawan (Universitas Sumatera Utara, 2024)
Social Forestry is a system of sustainable forest management implemented in state forest areas/private forests/customary forests by local communities or customary law communities as executors. This study aims to analyze the priority level of Human Resources (HR) capacity-building strategies in the Karya Lestari Farmers Group, Sibaganding Village, Girsang Sipangan Bolon District, Simalungun Regency. The research was carried out from September to November 2022 using primary and secondary data. The method used is the Analytical Hierarchy Process (AHP) using the Software Expert Choice tool. The data collection method is the Focus Group Discussion (FGD). Based on the results of the AHP, the priority of the HR capacity-building strategy is the criteria for increasing group knowledge in managing business potential to produce products that have good selling value and sell well in the market in the first place. The criteria for applying to the relevant agency to be included in group business management training activities are in second place and the criteria for establishing cooperation with related parties to help introduce group business products are in third place. Alternative aspects of institutional management are in first place, alternative aspects of area management are in second place and alternative aspects of business management are in third place.